Using monitors to monitor ecological restoration: Presence may not indicate persistence - Cross, Sophie; Craig, M.D.; Tomlinson, Sean; Dixon, Kingsley; Bateman, Bill (WILEY, 2020)
Habitat loss is a leading cause of biodiversity declines globally, and there has been increasing recognition in recent years of the importance of restoring degraded habitats to functional ecosystems to ameliorate this loss. Despite the critical roles animals play in ecosystems, animals are often overlooked in assessments of ecological restoration success, particularly beyond their presence or absence in these habitats. Apex predators are critical to ecosystems, regulating predator–prey dynamics, and in arid Australia, monitor lizards (Reptilia: Varanidae) often fill high-order predatory roles. Varanids are highly diverse in size and occupy a variety of ecological niches, providing an ideal group for assessing habitat change over multiple spatial scales. Here, we assess the responses of varanids to early-stage habitat restoration following the discontinuation of mining activities, by mapping behavioural signs of habitat usage including burrows, tracks and diggings. We recorded burrow size and track measurements to gauge the size of varanids utilising reference and restored habitats, and mapped tortuosity of tracks to assess their movement through habitats. Restored areas had significantly fewer signs of varanid presence than the reference bushland and largely appeared to be just traversed or used only by larger individuals. Restored landscapes, particularly those in early successional stages, often lack established vegetation cover and present increased metabolic costs and predation risks. Providing fauna refuges (e.g. hollow logs) to mitigate the metabolic costs and predation risks in areas undergoing restoration may aid in facilitating the return of varanids and of other animal populations, particularly during the early stages of vegetation establishment. Understanding the behavioural responses and movement ecology of animals within landscapes undergoing restoration is key to facilitating the conservation of self-sustaining and functional ecosystems.